Alcohol Consumption and Management Strategies Among Gay Bar Patrons in San Francisco and Oakland, CA. (March 2019) - Lin, Jessica; Hecht, Jennifer; Plenty, Albert H.; Siedle-Khan, Bob; Zamudio-Haas, Sophia; Ayala, Alicia; Charlebois, Edwin D.
Despite significant attention on gay men's substance use, much remains unknown about how environmental factors may contribute to gay men's elevated drinking patterns. We undertook a qualitative study of 51 gay bar patrons in San Francisco and Oakland, CA, in an effort to better understand the context of drinking motivations and management within the gay community in San Francisco and Oakland and to identify areas for potential interventions to encourage drinking moderation. A thematic analysis framework guided the process used to identify overarching themes and organize data around the social ecological framework. A focus on drinking motivations and management strategies emerged as a recurring theme across interviews. In this article, we describe alcohol consumption and management strategies that suggest that gay bar patrons experience encouragement from the individual, interpersonal, community, and structural levels to drink and that environmental and internal motivators for drinking often override participant's intentions and individualized strategies for moderation. Our findings suggest an unmet need for assistance in helping men to create effective harm reduction strategies around drinking, as well as an opportunity for creating interventions that address community- and structural-level motivators for drinking and management.